Green computing knowledge and practices among STML students in UUM - Ou, Xue Wei; Yaacob, Noorulsadiqin Azbiya (2015)
Green computing, also known as green IT is an environmentally sustainable computing. Environmental impacts of computer system and related resources can be minimized effectively through the practices of green computing.As a vast users of IT and computing, university students must have the knowledge in order to involve in liable practices of computing.Researches that deliver green computing in context of students in Malaysia is very limited, this paper aims to determine and differentiate the level of knowledge in green computing and green computing practices among university students based on gender.This paper is examined in the School of Technology Management and Logistics (STML), one of the faculties in Universiti Utara Malaysia (UUM).The data was collected via questionnaire survey targeting STML students, and being processed with SPSS v.22 statistical technique.The results of descriptive analyses show moderate knowledge of green computing knowledge and their computing practices also adhered to their knowledge, while independent-samples t-test analyses show no significant difference of green computing knowledge and practices between genders.It is concluded that gender does not influence green computing knowledge and practice of STML students. Future research should look into how the green computing knowledge affect students’ practices of green computing.